PERUBAHAN PENGATURAN PERUNTUKAN KAWASAN DALAM HUKUM PENATAAN RUANG (Studi Politik Hukum Atas Kebijakan Penataan Ruang Kota Malang) - Wahjuono, Tulus (De Jure: Jurnal Hukum dan Syari'ah, 2014)
This research aims to analyze the changes of area designation rule of spatial law in Malang, its causes, and its implications for legal politics. This research used a juridical-empirical approach. Data analyzed using interactive and content analysis. The results showed that the changes of area designation rule of spatial law in Malang based on a factors of spatial law issues and its deviation in the field, both legal and non-legal condition. The changes of area designation rule of spatial law in Malang which are not based on the principle of good environmental governance had an impact on legal politics that not aligned the product of spatial law to both progressive law nor responsive law. It will lose its legitimacy, either philosophical, juridical, and sociological in the society.